Treatment efficiency of patients with shin fracture after intraosseous blocked osteosynthesis by using the load dispenser - Yu. V. Sukhin; Yu. Yu. Pavlychko; P. V. Danilov (Patologìâ)
The purpose of research: еvaluation of the effectiveness of the device for determining the value of the load on the lower extremity while walking in real time with controlling and signalization of excessive and insufficient load.